A STUDY ON THE CODE SWITCHING IN CONVERSATIONS BETWEEN THE SECOND YEARS STUDENTS OF JUNIOR HIGH SCHOOL - Maria Desidaria Noge (STKIP Citra Bakti, 2019)
This research aimed at finding out: (1) whether the students use code switching in conversations; (2) the types of code switching used in conversations between the second year students of Junior High School; (3) the reasons why the students switch their language during the conversations. This research used descriptive method. Subject of the research was the second year students of SMPS Yos Soedarso Jerebuu. The result of this research was: (1) the students used the code switching in conversations (2) two types of code switching occurred during the conversation, there were: Intra-sentential Switching (IntraS) which is which occurred 7 times and Inter-sentential Switching (IntrS) which is the most frequently used (8 times) by the students during the English conversation, and (3) the reasons of students switched his or her language were: talking about particular topic which occurred 2 times, being emphatic about something which occurred 5 times, intention of clarifying the speech content for interlocutor which occurred 5 times, to soften or strengthen request or command which occurred once and because of lexical needs which occurred 4 times.